Innovation of swift: how it works – gains & risks - ROBERT, MR. P. WILLIAM; K, MS. SUBHASREE (The journal of contemporary issues in business and government, 2020)
The research paper titled “Innovation of SWIFT: How It Works – Gains & Risks” explores the various aspects of the interbank transfer worldwide including the gains and opportunities along with the risks involved in such transactions. Descriptive research is applied using Snowball sampling with 117 respondents. The tools used for the study are frequency analysis, mean analysis, factor analysis, independent t-test and ANOVA. It is found that six major factors which influence SWIFT are services, control, comprehensive, features, efficiency, attributes. There is no significant difference between SWIFT awareness of customers with respect to perception of SWIFT and is a significant difference between Gender with respect to the variable Service, Control and Attributes. Moreover there is a significant difference between interbank transfers with respect to Control. Also there is a significant difference between education with respect to efficiency and Income with respect to control, comprehensive and efficiency. Moreover there is a significant difference between occupation with respect to services, control and comprehensive.